O processo de aquisição da escrita na deficiência intelectual leve: um estudo de caso - Teles, Sabrina Lourenço (2019)
This research is a case study which proposes to analyze the process of written language acquisition of a ten year old subject, who has light Intellectual Deficiency (ID) in order to verify how literacy, through textual productions, influences learning when memory is compromised. Besides that, this study aims to contribute to formal teaching and learning of people with ID. In the pedagogical work, the difficulty is to awaken the interest of such students to learn writing and reading. It can be light, moderate or severe. This thesis is theoretically based on the socio- historical-cultural perspective, where language is understood as interaction, based on historical, social, cultural and biological aspects, being acquired and perfected in interaction scenes built in discursive relations between human beings. This conception shows the social nature of language which results from collective constructions through interactional processes. From the studies of Vygotsky, the language is seen as a constitute factor of the human being, having social and communicative functions, allowing contact between individuals and the perpetuation of culturally determined forms through language use. The sociointeractionist character of language is also included, which means it cannot be separated from its speakers, their productions and social contexts surrounded by ideological values. This conception includes the category of Textual Linguistics, once it considers the study of words, sentences related to a text as a whole unit, the social-historical context of production, and the language users as text producers. When we produce a text, we are making use of social language, materialized into different production, generator of textual or discursive genres determined by their conditions of production and their producers. Out text analyzes consider the social, cultural and biological conditions of texts producers, and the specificities involved in the process of developing the written language of the intellectual deficient. In order to do this, this research is based on the writings of Vygotsky (1997), Pino (2005), Pfanner and Marcheschi (2008), Braggio (1995), Aubarre (1997) and others.Specifically about the cognitive development of learning, we went to Consenza and Guerra (2011), Lent (2005), Bear (2008). To talk about language acquisition, we based the study on Vygotsky (2007, 2008) and regarding literacy, we relied on Kleiman (1995). In the analysis of the research material concerning Textual Linguistics, we used the works by Koch and Travaglia (1993), Koch (1987, 2011, 1989), among others. The criteria for the analysis of the written text was established considering the level of linguistic knowledge about words, sentences and grammar elements to the writing of coherent and cohesive texts. Also, we analyzed the questionnaires answered by B, the subject’s mother, by the teachers and the auxiliary teachers. The questions were directed to the investigation of social, school and familiar influences in the subject’s life. The results make clear that the more the environments organize themselves to stimulate the development of a person with light ID, the bigger the possibilities of this person being emancipated and adjusting in the existing social configuration.